Строение стебля эфемеров сем.brassicaceae burnett (SCIENCE and SOCIETY, 2023)
11 species of the Brassicaceae family growing was studied in the Kyzylkum desert. The features of the structure of the stems were revealed, the stem of most ephemera species is pubescent with different types of trichomes, often branched and glandular, characteristic of the family. The surface of the stem is often ribbed. The main function of the ephemeral stem, in addition to conducting, is the preservation of moisture due to the adaptive features of the cortex and accumulation in the cells of the core.